Deficiency of MGAT2 increases energy expenditure without high-fat feeding and protects genetically obese mice from excessive weight gain - David W. Nelson; Yu Gao; Nicole M. Spencer; Taylor Banh; Chi-Liang Eric Yen (Journal of Lipid Research, 2011)
Acyl CoA:monoacylglycerol acyltransferase 2 (MGAT2) is thought to be crucial for dietary fat absorption. Indeed, mice lacking the enzyme (Mogat2−/−) are resistant to obesity and other metabolic disorders induced by high-fat feeding. However, these mice absorb normal quantities of fat. To explore whether a high level of dietary fat is an essential part of the underlying mechanism(s), we examined metabolic responses of Mogat2−/− mice to diets containing varying levels of fat. Mogat2−/− mice exhibited 10−15% increases in energy expenditure compared with wild-type littermates; although high levels of dietary fat exacerbated the effect, this phenotype was expressed even on a fat-free diet. When deprived of food, Mogat2−/− mice expended energy and lost weight like wild-type controls. To determine whether MGAT2 deficiency protects against obesity in the absence of high-fat feeding, we crossed Mogat2−/− mice with genetically obese Agouti mice. MGAT2 deficiency increased energy expenditure and prevented these mice from gaining excess weight. Our results suggest that MGAT2 modulates energy expenditure through multiple mechanisms, including one independent of dietary fat; these findings also raise the prospect of inhibiting MGAT2 as a strategy for combating obesity and related metabolic disorders resulting from excessive calorie intake.